IMPLEMENTASI HKI PADA PRODUK UNGGULAN IKM SEKTOR MAKANAN DI KOTA MADIUN UNTUK BERSAING DALAM MASYARAKAT EKONOMI ASEAN - Farida Styaningrum; Indriyana Dwi Mustikarini (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Intellectual Property Rights (IPRs) on excellent product of Small and Medium Industry (SMI) food sector in Madiun can encourage business development and provide a competitive advantage when entering in ASEAN or AEC free trade. This research aims to determine the implementation of IPRs by Industry Sector, Department of Manpower of Madiun on excellent product of SMI food sector, perception of SMI food sector perpetrator to IPRs, and obstacles faced in the implementation of IPRs on excellent product of food sector in Madiun to compete in AEC. The approach method used is qualitative descriptive. The results showed that the Industry Sector, Manpower Office of Madiun in implementing IPRs on excellent product of SMI food sector in Madiun to compete in AEC less effectively. SMI in the food sector in Madiun assume that IPRs is not so important to compete in the MEA. The obstacles faced in the implementation of IPRs on excellent product of SMI food sector in Madiun to compete in AEC: SMI data of incomplete food sector, limited number of SMI food sector in registration of IPRs, socialization of IPRs less effective, lack of understanding of perpetrator SMI on IPRs, and the lack of appreciation of SME actors against IPRs, lack of understanding of SMI actors concerning IPR, and lack of appreciation of SME actors against IPR